An Analysis of Speech Acts in Think Globally Act Locally Textbook For 9th Grade Studentsa - Hafidzhatu Zhahira Syahwa; Elisa Nurul Laili (International Journal of Research in Education, 2026)
This research is motivated by the importance of pragmatic competence in English language learning at the junior high school level, where students often master grammatical structures but struggle to interact naturally in real-life situations. There is a noticeable gap in textbooks which frequently emphasize linguistic aspects over sociopragmatic dimensions. The purpose of this study is to identify the types of speech acts, describe their realization across various text types, and examine their potential in supporting students' pragmatic competence within the 9th-grade English textbook "Think Globally Act Locally." The method employed is qualitative content analysis with a library research approach. Data in the form of utterances from the textbook were collected through document observation and note-taking techniques, then analyzed using Searle’s classification of speech acts. The research findings reveal four types of speech acts: Directives, Expressives, Representatives, and Commissives. Directives emerged as the most dominant type (49.4%), reflecting the instructional nature of the textbook. The realization of these speech acts highly depends on the text genre; for instance, Directives appear as imperatives in procedure texts, while Expressives are frequently found in interpersonal dialogues. In conclusion, this textbook holds significant potential for supporting pragmatic competence through rich situational contexts, although explicit explanations regarding politeness strategies remain limited.